Visual Evaluation of Tree Health in Belgrade’s Urban Forest: Čukarica Case Study - Suzana Ž. Mitrović; Milorad M. Veselinović; Nevena M. Čule; Snežana A. Stajić; Goran D. Češljar; Renata P. Gagić-Serdar; Marija D. Milosavljević (HortScience)
A visual assessment of tree conditions is essential for public safety and health because urban trees increase attractiveness and provide other benefits, including reducing global warming and air filtration. Unhealthy or damaged trees pose a concern, emphasizing the importance of comprehensive inspections to identify hazards such as decay or dead branches. The assessment of the trees within the green infrastructure of the brownfield in Belgrade, Serbia, indicated that 35.1% of the examined trees failed to satisfy the basic preservation standards, emphasizing the necessity for proactive strategies for management.